THE IMPACT OF APPLYING ENGLISH SONG IN LISTENING COMPREHENSION - Murniaty Murniaty (Journal MELT (Medium for English Language Teaching), 2019)
The study investigated about the sluggishness of students in English language lesson that caused them have low score. Due to that reason, it had researched teaching and learning process of listening comprehension. The students of one public junior high school, class VII were trained to listen songs as an experiment for several times in one semester, such as : folk songs, pop songs, etc. The research findings by applying Wilcoxon signed-rank test showed that Z > 1,96, that is Z > 5,147; which means there is significant difference after giving the treatment, or the score raised up about 5 – 10%. This indicates that students more understand  the substance of the song also other English language materials, and more attractive and courage  to learn English language.